Family history of venous thromboembolism in the paediatric population: The need for a standardized definition. Issue 173 (January 2019) - Hau, Anna; Wegener, Eric; Ignjatovic, Vera; Revel-Vilk, Shoshana; Monagle, Paul
Abstract: Positive family history is known to be an independent risk factor for venous thromboembolic (VTE) that may or may not reflect an underlying hereditary disorder. However, there is no clear standardized definition of what constitutes a positive family history for VTE in children. We aimed to assess the current published definitions of positive family history as a risk factor for VTE in children and ascertain if any consensus exists. Methods: We conducted a literature review through two major databases PUBMED and EMBASE (1969–June 2018). Three different search statements were used for each database to maximize the number of relevant results, giving rise to 1050 non-duplicated papers. Results: Of the 1050 papers, 32 articles demonstrated 18 separate definitions on what constitutes a positive family history in paediatric studies. Variations in definitions were related to the closeness of kinship (first or second-degree relatives), whether thrombosis was provoked or unprovoked, the age of presentation of thrombosis in the kinship, and clinical vs. laboratory definition of positive family history. Of the definitions, 1st degree relative/s developing VTE at any age whether provoked or unprovoked was most commonly described. Conclusion: According to this literature review, the definition of a positive family history in paediatric populations is non-standardized amongst current published papers. To enable accurate comparisons across studies and improve clinical risk assessment, we therefore propose the need for a standardized definition of what constitutes a positive family history. Highlights: Positive family history is a known independent risk factor for venous thromboembolic. There is no current consensus on the definition of family history as a risk factor in paediatric VTE. We propose the need for a standardized definition of positive family history to improve risk stratification of paediatric VTE.